PLASMA ADRENOMEDULLIN AND PROADRENOMEDULLIN N-TERMINAL 20 PEPTIDE (PAMP) IN RESPIRATORY DISEASES - HIGA, Toshinobu; KUMAMOTO, Kenshi; ISHIBATAKE, Hideaki; ETO, Tanenao; ONIZUKA, Reiko; KITAMURA, Kazuo; SHIMOKUBO, Toru; TANAKA, Masayuki (Japanese Journal of National Medical Services, 1998)
Potent vasorelaxant peptides, adrenomedullin (AM) and PAMP, are reported to have a bronchodilatory effect. To elucidate that AM and PAMP are involved in respiratory regulation, we have measured plasma concentrations of AM and PAMP in chronic respiratory diseases and asthmatic attack. The plasma concentrations of AM and PAMP in various chronic respiratory diseases were higher than those in normal control subjects. The plasma levels of these peptides in chronic respiratory diseases were increased in proportion to the severity of respiratory failure. Furthermore, in patients with pulmonary emphysema and chronic bronchial asthma, the plasma concentrations of AM and PAMP inversely correlated with the arterial PO2. In bronchial asthma, the plasma levels of AM and PAMP in the attack were significantly higher than those in the remission. These results suggest that AM and PAMP participate in the compensatory mechanisms against pulmonary diseases through their effects of pulmonary vasorelaxation and bronchodilatation.